Modelling the end-use performance of alternative fuel properties in flex-fuel vehicles. (1st October 2022) - Kroyan, Yuri; Wojcieszyk, Michał; Kaario, Ossi; Larmi, Martti
Highlights: Developed model shows the impact of fuel properties on flex-fuel engine performance. The model outcomes represent fuel consumption changes over driving cycles. The effect of the most significant fuel properties on fuel consumption revealed. Fuel economy of alternative fuels in flex-fuel engines compared to regular engines. The performance of renewable gasoline blendstocks simulated using the developed model. Abstract: Renewable fuels and fuel-optimized engines play a key role in the time- and cost-effective decarbonization of current mobility. The present work introduces a state-of-the-art mathematical model that allows for the first time an accurate estimation of fuel consumption in flex-fuel vehicle engines by considering the impact of the most significant fuel properties exclusively. These engines are optimized to a higher concentration of non-drop-in fuels such as E85. Based on the literature data, a matrix was built with fuel properties as multiple independent variables and fuel consumption as a response variable. A multilinear regression with quantitative analysis was applied to develop a fuel consumption model for FFVs. The most significant fuel properties turned out to be octane sensitivity, vapor pressure, lower heating value, and density. All properties in the final model have a unique and important impact on fuel consumption, secured by extremely low p-values (P ≪ 1 %). The model reached very high accuracy represented by R-Square of 0.994, which turned into 1.41 % of the average absolute error in internal validation and only 1.9 % in external validation. The present study shows that in all alternative fuel cases, flex-fuel vehicles performed with better fuel economy than standard spark-ignition light-duty vehicles. Moreover, high concentration alcohol blends reduce energy consumption as well as tank-to-wheel CO 2 emissions despite their higher fuel consumption. The developed model can be applied to fuel consumption estimations in FFVs from single chemical compounds to commercial fuel products including new fuel blends.